The Relationship of Learning of ASKEB II Course Practicum Laboratory With the Achievement of Level II Students' Competence - Suryani, Elvi; Harahap, Maryam Latifah; Siregar, Rahmah Juliani; Ihram Kurnia Agusta (PT Inovasi Pratama Internasional, 2022)
Practical learning is a process to improve the skills of participants by using various methods according to the skills provided and the equipment used. This type of research is descriptive analytic with a cross sectional approach. Data analysis was performed using the chi square formula. The results showed that from the results of the cross table between laboratory practicum learning and competency achievement, the majority of both categories were good, namely as many as 22 people (39.3 %), the majority category was sufficient, namely 15 people (26.8%). And the less majority category is sufficient, namely 2 students ( 3.6 %). The results of statistical tests with the Chi-Square test showed that the value of X 2 count (22.485) > (9.488) and the value of p = 0.000 < 0.05 . It means that Ho is rejected and Ha is accepted, so that there is a relationship between laboratory practicum learning for the Askeb II subject and the achievement of competence level II students. The conclusion of this study is that bivariate analysis with the Chi-Square test is known to have a relationship between laboratory practicum learning for the Askeb II subject and the achievement of competence level II students.